Overcoming language barriers in film production: the role of VR-based learning in English proficiency - Piayura, Orathai; Boonmas, Thidarat; Wongphongkham, Niyom; Sae-joo, Phongthanat; Narongchai, Wanichcha; Wongphongkham, Hava; Promphakping, Buapun; Rahman, Md Ahbabur (Frontiers in Education, 2025)
Virtual Reality (VR) has promptly transformed educational practices, presenting immersive environments that boost learning experiences. However, it must be noted that even though earlier research highlights the possible role of VR in language learning as a viable medium, it still stands as a largely unexplored area due to lack of understanding of its potential and limitations. This research is fueled by the shift toward using digital educational resources during the time of the corona virus pandemic and it focuses on the contribution of VR toward the improvement of English skills within the context of the film industry in Thailand. The study created a VR App called “EngLab for Film” that has 10 interactive units related to film making. Using structured questionnaires, quantitative data were collected and analyzed with SPSS to assess engagement, motivation, and independent learning outcomes. Findings reveal that VR-based learning fosters motivation and enhances vocabulary acquisition, offering a dynamic alternative to traditional methods. However, technical limitations, such as video clarity, require further refinement. This study underscores VR's transformative potential in language education, providing actionable insights for its integration into specialized professional contexts. The findings indicate that VR can significantly enhance language skills and motivation, though technical and content-related improvements are needed.